Safety of Lumason® (SonoVue®) in special populations and critically ill patients - Filippone, A.; Kirchin, M. A.; Monteith, J.; Storto, M. L.; Spinazzi, A. (Frontiers in Cardiovascular Medicine, 2023)
Evidence for the safe use of Lumason ® , an ultrasound enhancing agent (UEA), in special patient populations is critical to enable healthcare professionals to make informed decisions concerning its use in such patients. Herein, we provide insight on the safety and tolerability of Lumason ® in special patient populations. Findings are presented from clinical pharmacology studies conducted in patients with compromised cardiopulmonary conditions, from a retrospective study performed in critically ill patients, and from post-marketing surveillance data from over 20 years of market use of Lumason ® . No detrimental effects of Lumason ® on cardiac electrophysiology were observed in patients with coronary artery disease (CAD), and no significant effects on pulmonary hemodynamics were noted in patients with pulmonary hypertension or congestive heart failure. Similarly, no effects on several assessments of pulmonary function (e.g., FVC) were observed in patients with chronic obstructive pulmonary disease (COPD), and no clinically meaningful changes in O2 saturation or other safety parameters were observed after administration of Lumason ® to patients with diffuse interstitial pulmonary fibrosis (DIPF). The retrospective study of critically ill patients revealed no significant difference for in-hospital mortality between patients administered Lumason ® for echocardiography versus those who had undergone echocardiography without contrast agent.Post-marketing surveillance revealed very low reporting rates (RR) for non-serious and serious adverse events and that serious hypersensitivity reactions were rare. These findings confirm that Lumason ® is a safe and well tolerated UEA for use in special populations and critically ill patients.